Recent advances in the synthesis and applications of mordenite zeolite – review. Issue 1 (23rd December 2020) - Narayanan, S.; Tamizhdurai, P.; Mangesh, V. L.; Ragupathi, C.; Santhana krishnan, P.; Ramesh, A.
Abstract : Among the many industrially important zeolites, mordenite is found to be interesting because of its unique and exceptional physical and chemical properties. Abstract : Among the many industrially important zeolites, mordenite is found to be interesting because of its unique and exceptional physical and chemical properties. Mordenite (high silica zeolite) is generally prepared by the hydrothermal method using TEA + cations. TEA + cations are the best templating agent, though they can create a number of issues, for instance, generating poison and high manufacturing cost, wastewater contamination, and environmental pollution. Hence, it is necessary to find a mordenite synthesis method without using an organic template or low-cost template. In this review, a number of unique sources were used in the preparation of mordenite zeolite, for instance, silica sources (rice husk ash, silica gel, silica fumes), alumina sources (metakaolin, faujasite zeolite) and sources containing both silica and alumina (waste coal fly ash). These synthesis approaches are also based on the absence of a template or low-cost mixed organic templates (for instance, glycerol (GL), ethylene glycol (EG), and polyethylene glycol 200 (PEG)) or pyrrolidine-based mesoporogen ( N -cetyl- N -methylpyrrolidinium) modifying the mordenite framework which can create unique properties. The framework properties and optical properties (indium-exchanged mordenite zeolite) have been discussed. Mordenite is generally used in alkylation, dewaxing, reforming, hydrocracking, catalysis, separation, and purification reactions because of its large pore size, strong acidity, and high thermal and chemical stability, although the applications are not limited for mordenite zeolite. Recently, several applications such as electrochemical detection, isomerization, carbonylation, hydrodeoxygenation, adsorption, biomass conversion, biological applications (antibacterial activity), photocatalysis, fuel cells and polymerization reactions using mordenite zeolite were explored which have been described in detail in this review.